2001
DOI: 10.1074/jbc.m104265200
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Macrophage Colony-stimulating Factor Receptor on Microglial Cells Induces an Inflammatory Response

Abstract: Microglia are important in the inflammatory response in Alzheimer's disease (AD). We showed previously that macrophage colony-stimulating factor receptor (M-CSFR), encoded by the c-fms protooncogene, is overexpressed on microglia surrounding amyloid ␤ (A␤) deposits in the APP V717F mouse model for AD. The M-CSFR is also increased on microglia after experimental brain injury and in AD. To determine the relevance of these findings, we transiently expressed M-CSFR on murine BV-2 and human SV-A3 microglial cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
73
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 71 publications
2
73
1
Order By: Relevance
“…Control transfections were performed in parallel with an equal volume of LipofectAMINE PLUS reagent only (transfection medium; designated by M in the figures). Transfections using the pZeoSV plasmid (Invitrogen) that contains the pTK1 backbone sequence originally used in c-fms subcloning were included as a second control, although we previously showed that pZeoSV does not induce a microglial proinflammatory response (19). Cells were transfected with the pZeoSV plasmid using the same procedure as described for pTK1.…”
Section: Microglial Cell Lines Plasmid Transfections and Tissue Culmentioning
confidence: 99%
See 4 more Smart Citations
“…Control transfections were performed in parallel with an equal volume of LipofectAMINE PLUS reagent only (transfection medium; designated by M in the figures). Transfections using the pZeoSV plasmid (Invitrogen) that contains the pTK1 backbone sequence originally used in c-fms subcloning were included as a second control, although we previously showed that pZeoSV does not induce a microglial proinflammatory response (19). Cells were transfected with the pZeoSV plasmid using the same procedure as described for pTK1.…”
Section: Microglial Cell Lines Plasmid Transfections and Tissue Culmentioning
confidence: 99%
“…Immunocytochemical visualization of M-CSFR was demonstrated previously (19). To quantify cells overexpressing M-CSFR, 24 h post-transfection BV-2 cells were washed with PBS buffer, reacted for 1 h with 10% normal goat serum (Zymed Laboratories Inc.), and incubated with rabbit antimouse M-CSFR antiserum (1:500) (Upstate Biotechnology Inc., Lake Placid, NY) for 16 h at 4°C.…”
Section: Microglial Cell Lines Plasmid Transfections and Tissue Culmentioning
confidence: 99%
See 3 more Smart Citations